PERBANDINGAN KINERJA PORTOFOLIO GLOBAL MINIMUM VARIANSI BERDASARKAN EKSISTENSI KENDALA BOBOT ASET POSITIF - Nurwahidah Nurwahidah (HISTOGRAM: Jurnal Pendidikan Matematika, 2023)
Investors face high risk in stock investing. It is important to use investment strategies that can minimize risk and maximize return. Building a portfolio is a solution to minimize risk in investing. This sudy compares the perfomance of Global Minimum Variance Portfolio (GMV) without positive weight asset constraint and GMV with positive weight asset constraint. The perfomance of each portfolio is measured by sharpe ratio. The portfolio without positive weight asset builds by Markowitz method with traditional approachment, while the portfolio with positive weight asset builds by Markowitz method with quadratic programming approachment.Based on the conducted research, it describes that GMV potfolio with positive asset weight constrain shows a higher value of sharpe index than GMV portfolio without positive asset weight constraint. Thus, the study concludes that the GMV portfolio with positive asset weight constraint has better performance than the GMV portfolio wtihout positive asset weight constraint.